50 hikes with kids : Oregon & Washington - Gorton, Wendy (Timber Press, 2018)
"This guide to hiking with children has been handcrafted for Northwest parents, educators, and caregivers looking for the best 50 trails in the area to hike with kids. 50 Hikes with Kids: Oregon and Washington not only offers detailed hiking information with maps and keys to difficulty, but also adds a layer of fun with plant, wildlife, and natural history to foster kids' genuine lifelong curiosity in our region's flora, fauna, and geology"--